Pollution trace gases C 2 H 6 , C 2 H 2 , HCOOH, and PAN in the North Atlantic UTLS: observations and simulations - Wetzel, Gerald; Friedl-Vallon, Felix; Kretschmer, Erik; Maucher, Guido; Nordmeyer, Hans; Oelhaf, Hermann; Orphal, Johannes; Piesch, Christof; Sinnhuber, Björn-Martin; Ungermann, Jörn; Vogel, Bärbel; Glatthor, Norbert; et al. (Atmospheric Chemistry and Physics, 2021)
Measurements of the pollution trace gases ethane (C2H6), ethyne (C2H2), formic acid (HCOOH), and peroxyacetyl nitrate (PAN) were performed in the North Atlantic upper troposphere and lowermost stratosphere (UTLS) region with the airborne limb imager GLORIA (Gimballed Limb Observer for Radiance Imaging of the Atmosphere) with high spatial resolution down to cloud top. Observations were made during flights with the German research aircraft HALO (High Altitude and LOng Range Research Aircraft) in the frame of the WISE (Wave-driven ISentropic Exchange) campaign, which was carried out in autumn 2017 from Shannon (Ireland) and Oberpfaffenhofen (Germany). Enhanced volume mixing ratios (VMRs) of up to 2.2 ppbv C2H6, 0.2 ppbv C2H2, 0.9 ppbv HCOOH, and 0.4 ppbv PAN were detected during the flight on 13 September 2017 in the upper troposphere and around the tropopause above the British Isles. Elevated quantities of PAN were measured even in the lowermost stratosphere (locally up to 14 km), likely reflecting the fact that this molecule has the longest lifetime of the four species discussed herein. Backward trajectory calculations as well as global three-dimensional Chemical Lagrangian Model of the Stratosphere (CLaMS) simulations with artificial tracers of air mass origin have shown that the main sources of the observed pollutant species are forest fires in North America and anthropogenic pollution in South Asia and Southeast Asia uplifted and moved within the Asian monsoon anticyclone (AMA) circulation system. After release from the AMA, these species or their precursor substances are transported by strong tropospheric winds over large distances, depending on their particular atmospheric lifetime of up to months. Observations are compared to simulations with the atmospheric models EMAC (ECHAM5/MESSy Atmospheric Chemistry) and CAMS (Copernicus Atmosphere Monitoring Service). These models are qualitatively able to reproduce the measured VMR enhancements but underestimate the absolute amount of the increase. Increasing the ...